INTEGRATION OF SHARIA FINANCIAL LITERACY INTO THEMATIC LEARNING FOR THE PEWANIDA MUSLIM COMMUNITY IN MALAYSIA. - Siti Kadariah; Rahmat Daim Harahap; Emi Masyitah; Yuli Arnida Pohan; Farida Ulvi Na’imah; Nur Dinah Fauziyah; Putri Nazli; Puan Zalhra Binti Puteh; Dea Ananda (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2026)
Sharia financial literacy levels among Muslim households in minority or diaspora communities remain low. Previous studies indicate that many Muslim communities struggle to distinguish between conventional financial products and those compliant with Sharia principles (OECD, 2023; Isa et al., 2024). To address this issue, an integrated educational model has been introduced to leverage local socio-religious potential, strengthen household financial resilience, and enhance Sharia financial inclusion. Although the Pewanida (Women's Association) community in Malaysia consistently participates in religious gatherings, many members still face challenges regarding conceptual understanding, contract governance, managerial capacity, and competitiveness vis-à-vis conventional financial systems. This study employs a qualitative approach—utilizing semi-structured interviews with academic experts from Universitas Potensi Utama and representatives of the Pewanida community in Malaysia—to analyze the implementation of thematic Quranic learning integrated with Sharia financial literacy. The findings reveal that program sustainability relies heavily on community leadership, while misconceptions regarding *Murabahah* financing and limited understanding of formal Sharia financial services remain significant challenges. Therefore, strengthening institutional support and developing a sustainable management framework are crucial for enhancing Sharia financial literacy and fostering community economic resilience.